Remote Microcontroller Scanner Design for STM32 Microcontrollers Used to Distance Education Form - Jacko, Patrik; Guzan, Milan; Kalinov, Andrii (2021 IEEE International Conference on Modern Electrical and Energy Systems (MEES), 2021)
The novel coronavirus disease (Covid-19) is a global problem that has caused many changes in people's lives. One of the problems is distance education, that has caused a difficulty form of study. Students often do not have required study components, because they are in the home and teacher does not have complete control over them. This paper described remote control and monitor system for the microcontroller technique subject, where the teacher gets possibilities for monitoring each student's microcontroller program. The subject is focused to the basic peripherals and functionalities of STM32 microcontrollers and internet communication based on the ESP8266 chip. Therefore, the article contains of monitoring module design, remote control application and simple test of the remote-control scanner for STM32 microcontrollers focused to the distance form of study.